E o que viu testemunha: o conceito de testemunha a partir do Evangelho de João 19,35 - Fraguas, Eduardo Bueno (2012)
The concept of witness (martyr) has enhanced throughout history. This term has been habitually utilized both inside civilian and religious environment, however for Christian language, its root is of the essence of what is "bear witness"; in particular, what presents the Gospel. This paper presents a reflection on the concept of witness and its evolution, beginning with the development of this term in Greek culture, from the Old Testament and Jewish culture to reach the New Testament. The center of this reflection is the Gospel of John, with a focus on chapter 19 verse 35: And he who has seen has borne witness . This has been presented by Johannine Tradition and posteriorly by Church History development. The testimony is the key to biblical language and therefore also becomes something essential for today´s Christians